Efficacy and safety of a fatty acid amide hydrolase inhibitor (PF-04457845) in the treatment of cannabis withdrawal and dependence in men: a double-blind, placebo-controlled, parallel group, phase 2a single-site randomised controlled trial. (January 2019) - D'Souza, Deepak Cyril; Cortes-Briones, Jose; Creatura, Gina; Bluez, Grai; Thurnauer, Halle; Deaso, Emma; Bielen, Kim; Surti, Toral; Radhakrishnan, Rajiv; Gupta, Aarti; Gupta, Swapnil; Cahill, John; et al.
Summary: Background: Cannabis is one of the most widely used drugs worldwide. Cannabis use disorder is characterised by recurrent use of cannabis that causes significant clinical and functional impairment. There are no approved pharmacological treatments for cannabis use disorder. One approach is to potentiate endocannabinoid signalling by inhibiting fatty acid amide hydrolase (FAAH), the enzyme that degrades the endocannabinoid anandamide. We aimed to test the efficacy and safety of the FAAH-inhibitor PF-04457845 in reduction of cannabis withdrawal and cannabis use in men who were daily cannabis users. Methods: We did a double-blind, placebo-controlled, parallel group phase 2a trial at one site in men aged 18–55 years with cannabis dependence according to DSM-IV criteria (equivalent to cannabis use disorder in DSM-5). After baseline assessments, participants were randomly assigned (2:1) to receive PF-04457845 (4 mg per day) or placebo using a fixed block size of six participants, stratified by severity of cannabis use and desire to quit. Participants were admitted to hospital for 5 days (maximum 8 days) to achieve abstinence and precipitate cannabis withdrawal, after which they were discharged to continue the remaining 3 weeks of treatment as outpatients. The primary endpoints were treatment-related differences in cannabis withdrawal symptoms during hospital admission, and week 4 (end of treatment) self-reported cannabis use and urine THC-COOH concentrations in the intention-to-treat population. The study is registered atClinicalTrials.gov, numberNCT01618656 . Findings: Between Sept 12, 2012, and Jan 18, 2016, 46 men were randomly assigned to PF-04457845 and 24 to placebo. Adherence to study medication was 88%, as confirmed by video-calling and pill count, and corroborated by corresponding drug and anandamide concentrations in blood. Relative to placebo, treatment with PF-04457845 was associated with reduced symptoms of cannabis withdrawal (first day of treatment mean symptom score 11·00 [95% CI 7·78–15·57] vs 6·04 [4·43–8·24]; difference 4·96 [0·71–9·21]; padj =0·048; second day of treatment 11·74 [8·28–16·66] vs 6·02 [4·28–8·47]; difference 5·73 [1·13–10·32]; padj =0·035) and related mood symptoms during the inpatient phase. Additionally, treatment with PF-04457845 was associated with lower self-reported cannabis use at 4 weeks (mean 1·27 joints per day [95% CI 0·82–1·97] vs 0·40 [0·25–0·62]; difference 0·88 [0·29–1·46]; p=0·0003) and lower urinary THC-COOH concentrations (mean 657·92 ng/mL [95% CI 381·60–1134·30] vs 265·55 [175·60–401·57]; difference 392·37 [17·55–767·18)]; p=0·009). Eight (17%) patients in the PF-04457845 group and four (17%) in the placebo group discontinued during the treatment period. During the 4-week treatment phase, 20 (43%) of 46 participants in the PF-04457845 group and 11 (46%) of 24 participants in the placebo group had an adverse event. There were no serious adverse events. Interpretation: PF-04457845, a novel FAAH inhibitor, reduced cannabis withdrawal symptoms and cannabis use in men, and might represent an effective and safe approach for the treatment of cannabis use disorder. Funding: United States National Institute of Drug Abuse (NIDA).